Synthesis, molecular modeling and biological evaluation of two new chicoric acid analogs. Issue 4 (16th February 2017) - Righi, Giuliana; Pelagalli, Romina; Isoni, Valerio; Tirotta, Ilaria; Dallocchio, Roberto; Dessì, Alessandro; Macchi, Beatrice; Frezza, Caterina; Rossetti, Ilaria; Bovicelli, Paolo
Abstract: Two conformationally constrained compounds similar to chicoric acid but lacking the catechol and carboxyl groups were prepared. In these analogues, the single bond between the two caffeoyl fragments has been replaced with a chiral oxirane ring and both aromatic residues modified protecting completely or partially the catechol moiety as methyl ether. Preliminary molecular modelling studies carried out on the two analogues showed interactions near the active site of HIV integrase; however, in comparison with raltegravir, the biological evaluation confirmed that CAA-1 and CAA-2 were unable to inhibit infection at lower concentration. Abstract :